Current Status and the Development Prospects of Mediation in Russia as an Alternative Means for the Settlement of Economic Disputes - Hudoykina, Tatiana Viktorovna (International Journal of Economics and Financial Issues, 2015)
The article considers the current status and the ways for further development of mediation in Russia. A mediation procedure is considered as an effective and agile method for settlement of a number of economic conflicts, which can become a real alternative to state court proceedings. The concept of mediation is determined; its essence and nature is revealed as of an alternative procedure for settlement of differences between the parties with the assistance of an independent mediator; main distinctions from the public proceedings are indicated. Advantages of mediation are identified, of which it is necessary to inform the contemporary business community with the aim to actively implement this institute into practice. Based on the analysis of various experience of mediation, both Russian and foreign, proposals are made for perceiving in the Russian Federation certain positive trends in mediation procedure. The paper discloses the issues of mediators training and analyzes the statutory formalization of this institution in Russia. Gaps in regulation are revealed. Types of established and operating organizations in Russia to provide mediation and organizations for training mediators are disclosed. The positive experience of isolated constituent entities of the Russian Federation is studied. Common problems and reasons for inconsiderable use of dispute settlement procedure involving mediators in Russia are studied. Growth area for long-term development of mediation is determined. Keywords: mediation, alternative means, procedure, settlement, dispute, mediator. JEL Classifications: H72, H73, O24